ANALISIS SUMBER DAN PENGGUNAAN DANA PADA PT. SERMANI STEEL DI MAKASSAR - Basri Laita (AkMen JURNAL ILMIAH, 2013)
One that must be considered in the company's operations is the financial management function by using analysis of sources and uses of funds so that the company can run smoothly in achieving the maximum possible profit. In the report the importance of the sources and uses of funds in the research journal of concern to consume is the problem ah keuangaan reports that a major factor as well as support to ensure the continuity of the company's activities